Percutaneous Pedicle Screw and Rod Insertion for the Treatment of Thoracic and Lumbar Spine Fracture - Chaudhary, Pashupati; Karn, Navin Kumar; Shrestha, Bikram Prasad; Khanal, Guru Prasad; Rijal, Raju (Nepal Orthopaedic Association Journal, 2013)
Introduction: Standard techniques for lumbar pedicle screw and rod fixation involve open exposure and extensive muscle dissection. Percutaneous pedicle screw system minimises the morbidity associated with traditional open approaches without compromising the quality of spinal fixation. A preliminary experience with this device has been encouraging. The purpose of this study was to demonstrate operative techniques and experiences with percutaneous lumbar pedicle screw and rod insertion for internal fixation of the lumbar spine without use of Zig. Methods: It was hospital based retrospective interventional study done at the department of Orthopaedics, B.P. Koirala Institute of Health Sciences, Dharan, Nepal over a period of 2 and half years. The study enrolled 30 patients aged 18-55 years who had presented with traumatic fracture of thoracic and lumbar spine. All thirty patients underwent percutaneous pedicle screw and rod fixation and successful percutaneous single/two level fusions. The follow up period ranged from 6 to 24 months. Results: The study comprised of 25 males and 5 females. Average patient’s age was 36.5 years (range 18-55 years). The common mode of injury was fall from height, road traffic accident, physical assault followed by sports related injury. All patients were having unstable spine fracture without neurological deficit. Operation time, loss of blood, post operative pain was less in percutaneous method. Post operative rehabilitation was easier. Spinal fusion was achieved in all patients in 6 months to 1 year time. There was no post-operative neurological deficit, infection, implant failure. Conclusion: Our early experience suggests that Minimally invasive approaches for performing lumbar fusion, is able to achieve the same clinical results as conventional open procedures. DOI: http://dx.doi.org/10.3126/noaj.v3i1.9322 Nepal Orthopedic Association Journal 2013 Vol.3(1): 23-27